Polymorphism of the mannose-binding lectin gene in the Arctic indigenous populations of the Russian Federation - S. Yu. Tereshchenko; M. V. Smolnikova (Вавиловский журнал генетики и селекции)
Mannose-binding lectin (MBL) is a pattern recognizing acute-phase protein of the innate immunity system actively involved in the elimination of a wide range of pathogenic microorganisms by activating the lectin pathway of the complement system. A significant part of the human population has a congenitally low production level and/or low MBL activity due to the carriage of various MBL2 variants, which can modify the course of a wide range of infectious diseases. The genotype and haplotype frequencies of the MBL2 polymorphisms have significant population differences. So far, data on the prevalence of the MBL2 genotypes in indigenous populations of the Russian Arctic regions have not been available. The aim of the study was to analyze the frequency and ethnic specificity of the distribution of allelic variants of the MBL2 polymorphisms rs11003125, rs7096206, rs7095891, rs5030737, rs1800450 and rs1800451 and their haplotypes in the populations of the Taimyr Dolgans-Nenets region of the Krasnoyarsk territory (Nenets, Dolgans-Nganasans, Russians). Data on the genotype and haplotype frequencies of the MBL2 gene among indigenous peoples of the Russian Arctic territories was first obtained in the study. The HYPA haplotype prevalence associated with a high concentration of MBL amounted to 35.4 % for Russian newborns in Eastern Siberia, corresponding to the one for European populations (27–33 %). In newborns of the Arctic populations, the prevalence of HYPA haplotype was significantly higher than in Russians and amounted to 64 % for Nenets and 56 % for the DolgansNganasans, which is close to the one detected for the Eskimos and North American Indians (64–81 %). Populations of Nenets and Dolgans-Nganasans demonstrated a significantly lower prevalence of MBL-deficient haplotypes compared with Caucasians of Eastern Siberia (3.9, 6.4 and 21.3 % respectively). Isolated Arctic populations were suggested to experience some intracellular infections (tuberculosis, leprosy) historically later and, unlike Caucasoid populations, to retain the high activity of the lectin complement activation pathway formed in the early stages of human evolution.